Workplace surveillance: an overview - Ball, Kirstie (Labor history, 2010)
This article attempts to review the proliferation of research findings about surveillance in the workplace and the issues surrounding it. It establishes a number of points of departure when considering the issue of workplace surveillance, before reviewing some of the more critical issues. First, it establishes that organizations and surveillance go hand in hand; and that workplace surveillance can take social and technological forms. Personal data gathering, Internet and email monitoring, location tracking, biometrics and covert surveillance are all areas of development. There is also evidence that groups of employees are appropriating information and communication technologies to stare back at their employers, exposing unsavoury practices and organizing collectively, prompting new thinking about resistance. Organizations watch employees primarily to protect their assets, although the nature and intensity of surveillance says much about how a company views its employees. Workplace surveillance has consequences for employees, affecting employee well-being, work culture, productivity, creativity and motivation. If no alternative can be found, managerial attention to task design, supervisory processes, employees' expectations about monitoring, and an appraisal of the company's operating environment can mediate its downsides. It is argued that in many ways the normality of workplace surveillance, and the prevalence of arguments about how to 'do it better', make it difficult to radicalize. As part of what is seen as 'good' management practice, it can confer benefits on the employee if conducted in a humane, balanced way, and is considered on a case-by-case-organization-by-organization-basis. However, the introduction of broader debates around information use, rights, power and social structure highlights how surveillance in the workplace may serve to perpetuate existing inequalities and create new ones.